Analysing survival data from clinical trials and observational studies - Marubini, Ettore; Valsecchi, Maria Grazia (John Wiley, 2000)
A practical guide to methods of survival analysis for medical researchers with limited statistical experience. Methods and techniques described range from descriptive and exploratory analysis to multivariate regression methods. Uses illustrative data from actual clinical trials and observational studies to describe methods of analysing and reporting results. Also reviews the features and performance of statistical software available for applying the methods of analysis discussed.
Statistics in practice
Keywords: Statistics as Topic; Clinical Trials as Topic; statistika, zdravotnická statistika; biometrie; statistika jako téma; management, organizace a řízení zdravotnictví; klinické zkoušky jako téma; Biometry